Study of Test Anxiety and Its Related Factors in Students of Behbahan Faculty of Medical Sciences in 2018 - Rafi, Alireza; Darabiyan, Pouriya; Mohammad Zade, Mastore; Eskandari, Parisa; Shajirat, Zeinab (International Research in Medical and Health Sciences, 2020)
Introduction: Anxiety is a mental affair caused by anxiety or nervousness and is associated with the stimulation of the nervous system. One of the common types of anxiety is anxiety over the test, which is usually known as test anxiety. The test anxiety generally decreases performance and undermines students’ academic achievement. Nursing students also face a high level of anxiety. Since nursing students have been affected by many stresses during the years of study at the Nursing Faculty and high volume of courses is one of the most important causes of anxiety, this study aimed to determine the test anxiety and its related factors in students of the Behbahan Faculty of Medical Sciences was done. Methods: This is a descriptive correlational study that was conducted on 174 students of Behbahan Faculty of Medical Sciences in 2018 who were randomly selected among male and female students of four years of study in different fields of study Nursing, operating room and occupational health was selected. The criteria for entry into this study were satisfaction for participation in the study and one to eight-semester students from the faculty of nursing, operating room, and occupational health Behbahan Faculty of Medical Sciences. Graduation criteria for the completion of the questionnaire were incomplete. The data collection tools were demographic information and a test anxiety questionnaire (Sarason). Data were analyzed by SPSS software version 20 and descriptive and analytical statistics. Results: The sample consisted of 174 nursing and midwifery students (71 males (40.81%) and 103 females (59.2%) with a mean age of 21.10 ± 1.50. The mean test anxiety score of students was 15.49 ± 6.41. 50 students (28.73%) had mild test anxiety, 84 students (48.27%) had average test anxiety and 40 students (22.98%) had severe test anxiety. There was a significant relationship between the mean test anxiety with the academic year, gender, marital status, place of residence, and educational level (P <0.05). But there was no significant relationship between anxiety, academic field, and grade gained (P> 0.05). There was no significant correlation between the test anxiety score and the age of the subjects, and the correlation coefficient was negative. Conclusion: Considering the anxiety of the test at different levels in all students, the destructive effects of this anxiety on the health and performance of students; Effective planning and psychological interventions are suggested.